Growth Hormone Deficiency in a Dopa-Responsive Dystonia Patient With a Novel Mutation of Guanosine Triphosphate Cyclohydrolase 1 Gene. (May 2015) - Lin, Yu; Wang, Dan-Ni; Chen, Wan-Jin; Lin, Xiang; Lin, Min-Ting; Wang, Ning
Dopa-responsive dystonia is a rare hereditary movement disorder caused by mutations in the guanosine triphosphate cyclohydrolase 1 ( GCH1 ) gene. This disease typically manifests in dystonia, with marked diurnal fluctuation and a dramatic response to levodopa. However, growth retardation in dopa-responsive dystonia has rarely been reported, and the etiology of short stature is not clarified. Here, we report a 14-year-old patient with extremities dystonia and short stature. Treatment with levodopa relieved his symptoms and resulted in a height increase. We also investigated the mutation in GCH1 and the etiology of short stature in this case. Sequence analysis of GCH1 revealed a novel mutation (c.695G>T). Laboratory examinations and imaging confirmed the diagnosis of growth hormone deficiency. We conclude that our case reveals a rare feature for dopa-responsive dystonia and suggests a possible pathogenic link between growth hormone deficiency and dopa-responsive dystonia. We recommend levodopa as the first choice for treating dopa-responsive dystonia in children with growth hormone deficiency.